Activated Carbon as a Functional and Sustainable Filler in Composite Bipolar Plates For Fuel Cell Applications - Iswandi; Suherman; Tino Hermanto; Yopan Rahmad Aldori; Muhammad Idris; Abu Bakar Sulong (Automotive Experiences, 2026)
Bipolar plate is a key component that determines a fuel cell's performance and service life. Carbon-based polymer composite materials were developed as lightweight, easy-to-process alternatives to metal. The use of carbon-based fillers in polymer composites has grown rapidly as an alternative to bipolar plate materials in fuel cell applications, especially to meet performance targets set by the U.S. Department of Energy (DOE). DOE requires high electrical conductivity (≥100 S/cm in the in-plane direction and ≥10 S/cm in the through-plane direction), low density, adequate mechanical strength, and good corrosion resistance and chemical stability. Recent studies have shown that the addition of carbon fillers, such as graphite, carbon black, graphene, and activated carbon (AC), can increase electrical conductivity by forming conductive percolation networks in polymer matrices. This study evaluates the potential of AC from household waste in the form of coconut shells as fillers in polypropylene (PP) composites for bipolar plate applications. AC is synthesized through carbonization and activation processes, then mixed into a PP matrix with PP/AC compositions of 100/0, 90/10, 80/20, and 70/30 percent by weight. The focus of the study is the effect of composition variation on density and bending strength. The test results show that increasing the AC fraction tends to decrease the composite density. The maximum density was obtained at a 90/10 (by weight) PP/AC composition of 0.9 g/cm³, indicating more effective filling of the pore matrix by AC particles. On the other hand, bending strength shows a downward trend. The maximum flexural strength is achieved at an AC composition of 34.58 MPa at 10% weight, indicating optimal dispersion and stress transfer between the matrix and the filler. The addition of AC above the composition causes a decrease in bending strength due to potential particle agglomeration, cavities, and the limited mobility of polymer chains. Electrical conductivity tends to increase with the addition of AC due to the formation of a network of electrical currents between carbon particles within cavities, reaching a maximum of 5 S/cm at 30% by weight of AC. The electrical conductivity obtained showed better improvement than several research results on polymeric materials using the hot-press method, with a value of 1.7 S/cm, using graphite filler materials up to 60% by weight. These findings confirm that AC from coconut shells has the potential to serve as a sustainable filler for fuel cell bipolar plates, with an optimal composition that balances density and mechanical properties.